II—Paul Franks: German Idealism. Issue 1 (13th August 2015) - Franks, Paul
Abstract : German idealists regard Spinozism as both the realism that outflanks Kant's idealism and the source of the conception of systematicity with which to fortify idealism. But they offer little argument for this view. To fill the gap, I reconstruct arguments that could underlie Jacobi's and Pistorius's tentative but influential suggestions that Kant is or should be a Spinozist. Kant is indeed a monist about phenomena, but, unlike Spinoza, a pluralist about noumena. Nevertheless, it is arguable that the Third Antinomy can be solved by a more thoroughgoing Spinozistic monism. The resulting Spinozism outflanks Kant by acknowledging Jacobi's charge that philosophy annihilates immediacy and individuality, whereas Kant's commitment to things in themselves can seem a half-hearted attempt to avoid the charge. However, the German idealist contention is that only a synthesis of such a Spinozism with Kantian idealism can retrieve immediacy and individuality, thus overcoming nihilism.